An organic photoredox catalyst promoted para-selective C–H amination of aryl oximes. Issue 2 (12th December 2022) - Wang, Cheng; Zhang, Xue-jun; Zhao, Yan-Wei; Liu, Qianqian; Cheng, Hongli; Huang, Zhibin; Zhao, Yingsheng
Abstract : Direct C–H amination methods are essential because of the importance of aryl amine derivatives. Abstract : Direct C–H amination methods are essential because of the importance of aryl amine derivatives. Despite significant progress in transformation methods of a C–H bond to C–N bonds, a general route for para -selective C–H amination remains elusive. This manuscript reports a new method for para -selective C–H amination of aryl oximes through transient steric control. A preliminary mechanism study revealed an interaction between 2, 4, 6-triphenylpyrylium tetrafluoroborate (TPT) and oxime to form an active aromatic ring. Meanwhile, TPT sterically hindered the ortho, and meta -position C–H bonds, leading to a selective reaction of the pyrazole radical with the phenyl ring at a less hindered para -position, providing a new direction to achieve the para -selective C–H functionalizations.